Study on spatial variability of soil nutrient and the evaluation of soil quality based on GIS. Issue 4 (March 2020) - Xiao, Hai; Tan, Chunhong
Abstract: In this study, geostatistics and GIS were applied to analyze the spatial variability of soil nutrient and the soil quality combined with the research variability property and spatial data in research area. The purpose of this paper is to study the spatial variability regulations between soil quality conditions and soil nutrient. The results show that the spatial variability degree of organic matter (OM), total nitrogen (TN), available potassium (AK), available phosphorus (AP), alkaline nitrogen (AN) and pH is 42%, 33%, 31%, 67%, 58% and 13%. pH is weak variability, TN and AK is low variability, all OM, AP and AN are moderate variability. The spatial distribution of soil nutrient is different, but there are some relationships in partial area.